Origin of the material dependence of temperature coefficient of redox potential in conjugated polymers. (23rd February 2021) - Iwaizumi, Hiroki; Inoue, Dai; Yasuda, Takeshi; Moritomo, Yutaka
Abstract: The thermal coefficient α (= d V / d T ) of the redox potential ( V ) is an important physical parameter for thermal energy harvesting. To clarify the microscopic origin of α in conjugated polymers, we compared α and the physical quantity obtained by a quantum chemistry calculation in typical polymers with small monomer molecular weight. We observed a strong correlation between α and the number ( N active ) of the active atom, which is defined as the atom whose variation of the Mulliken charge (Δ q ) at the oxidation process is beyond a threshold (Δ q th ). We interpreted the material dependence of α in terms of N active, because active atoms have a significant effect on the configuration entropy of the surrounding solvent molecules.